Medullary and C3–C4 propriospinal pathways underlying mammalian forelimb movement control - Vishwas Jindal; Matteo M. Grudny; Daniel W. Wesson; David E. Vaillancourt; Shahabeddin Vahdat (Proceedings of the National Academy of Sciences, 2026)
Classic models associate goal-directed upper limb movements with cortical motor areas and balance control with the brainstem. However, recent rodent studies suggest that medullary regions and local spinal circuits also contribute to forelimb execution, leaving it uncertain if these findings apply to humans. Critically, the dynamic interactions among medullary motor regions, intersegmental spinal networks, and cortical sensorimotor areas during hand movement control remain poorly understood. Here, through functional MRI (fMRI) studies in humans and mice during forelimb movement tasks, we reveal topographically organized corticomedullary networks, comprising the lateral rostral medulla (Lat-RM) and caudal medulla (CauM), that regulate forelimb movement. In mice, the corticomedullary coupling in both CauM and Lat-RM increased systematically along a ventro-medio-dorsal gradient, with the strongest links to primary motor and premotor cortices. In humans, higher‐order sensorimotor regions drove the strongest connectivity with CauM and Lat-RM, while the more medially located medial rostral medulla remained weakly engaged. Furthermore, simultaneous brain-spinal fMRI revealed distinct functional territories within the human C3–C4 cervical spinal cord, with ventral regions exhibiting strong connectivity to the medulla and dorsal regions to lower cervical segments. Together, our findings identify a conserved corticomedullary network underlying forelimb movement control across species, while also uncovering variation in cortical involvement. They indicate the presence of an indirect pathway involving both the reticulospinal pathway and the C3–C4 propriospinal system, which contributes to fine hand motor control in the mammalian brain.